Vatnajökull mass loss under solar geoengineering due to the North Atlantic meridional overturning circulation - Yue Chao; Schmidt Louise Steffensen; Zhao Liyun; Wolovick Michael; Moore John C (Zenodo, 2021)
Dataset for the manuscript ‘Vatnajökull mass loss under solar geoengineering due to the North Atlantic meridional overturning circulation’ (submitted to Earth's Future ) Please see the README for details.